HAK WARIS ANAK HASIL KAWIN SIRI DALAM PERSPEKTIF KUH PERDATA DAN KOMPILASI HUKUM ISLAM - Muhammad Arganata Thamrin; Nason Nadeak; Leonito Ribeiro; Tajuddin (Collegium Studiosum Journal, 2026)
This research discusses the inheritance rights of children born from unregistered marriages (kawin siri) from the perspective of the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata) and the Compilation of Islamic Law (Kompilasi Hukum Islam). The focus of the study is directed at two issues: the legal status of children born from unregistered marriages and their inheritance rights under the two applicable legal frameworks. This study utilizes a normative legal research method with a qualitative approach, conducted through a literature review of the Civil Code, the Marriage Law, the Compilation of Islamic Law, the Constitutional Court Decision Number 46/PUU-VIII/2010, and relevant scientific literature. The results of the study indicate that children born from unregistered marriages are in a vulnerable legal position because their parents' marriage is not officially registered and is often difficult to prove. Under the Civil Code, a child can obtain legal status and inheritance opportunities if they can be proven to be a legitimate child or a legally recognized child born out of wedlock. Meanwhile, under the Compilation of Islamic Law, a child's inheritance rights from the father depend on proving a lineage (nasab) relationship that arises from a valid marriage. Consequently, a biological relationship alone is insufficient to establish inheritance rights; an acknowledged and provable legal relationship is strictly required.